(untitled) (Journal of Media studies, 2022)
This study analyzes Kazakhstan’s two educational scholarshipprograms designed for pursuing international education and graduates’contribution to national development. Our data suggests that Bolashak andNazarbayev University scholarship programs play an important role indeveloping local talent. Graduates of these scholarship programs are involved inimproving systems and practices in their workplaces, thereby contributing towider positive social and economic changes in the country. On the other hand,limited employment opportunities in some sectors of economy, low salaries andnegative bureaucratic culture limit graduates’ contribution to the common good.We believe that graduates’ inability to use the acquired knowledge and skills isassociated with low rates of economic development and its failure to keep upwith the development of human capital. Our findings highlight the criticalimportance of developing the economy in tandem with human capitaldevelopment to maximize the benefits of scholarship programs